Obronne rezydencje Lisów w północnej Małopolsce. Uwagi do problematyki badań - Kołodziejski, Stanisław (Acta Universitatis Lodziensis. Folia Archaeologica, 1994)
The studies on the elite of medieval Poland, that have recently made considerable progress, have resulted in numerous articles devoted to particular families of magnates. Historical studies are paralled by archaeological ones, the aim of which is to recognize remains of fortified residences erected in the centres of the estates by representatives of these families. In this article an attempt is made to demonstrate the need to combine the efforts of akin scientific disciplines in order to fully recognize the problems posed by the study of the elites of feudal Poland, their importance and their political and economic activity. One of the subjects which make it possible for the studies pursued by medievists and archaeologists alike to achieve satisfactory results is the problem of medieval residential and defensive architecture of the Lis family, since the leading role played by this family in the internal politics of the state of that time and its high economic status were also reflected in architecture. Owing to field investigations, six fortified residences built by the members of the Lis family have so far been revealed and at least partly recognized. Three of these (Krzelów, Kozłów and Klimontów) were located within a compact and extensive landed property stretching along the river Mierzawa, tributary of the Nida. It seems justifiable to think that owing to the results of a penetrating analysis of written records it will be possible to add a nearby feature at Książ Wielki, characterized by similar morphology, to this series of the family investments. Another compact estate owned by the Lis family is located in the north-western part of the medieval province of Kraków, with fortified residences at Koziegłowy and Mirów. The Bąkowiec castle situated nearby may also have been erected by the members of this family. The last fortified medieval residence of the Lis family, recognized in Little Poland, is located between the rivers Niedzica and Nida, away from the two estates mentioned above. Its remains in the shape of a typical motte are situated at a place called Czarnocin. The studies conducted so far show that the buildings, briefly characterized in the article, owe their origin to the growth of the Us family and to the forming of separate estates for its particular branches. An indispensable condition for the proper functioning of a new estate was the fortified residence of its owner, which guaranteed safety and efficient management of the estate and provided a seat commensurate with the status of the magnate. Further archaeological investigations are necessary in order to recognize fully the morphology of these buildings and to confirm the already observable similarities in their function and layout. The analogies noted so far refer mainly to the choice of the site for erecting the fortified residence. Most of them are located in wet low-lying meadows, which location had influenced strongly the morphology of the features in question. Other similarites, mentioned in the article, should be confirmed by results of further excavations. The combined studies of archaeologists and historians should aim at defining precisely the period when the buildings were in use and to indicate their founders and later owners.